2018
DOI: 10.1089/lap.2018.0208
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Thunderbeat and Other Energy Devices in Laparoscopic Colorectal Resection: A Single-Center Experience

Abstract: Our dataset has the largest number of cases comparing TB and other energy devices in laparoscopic colorectal cancer surgery. They all appear to be equally safe and effective. Operating the TB device does not require a steep learning curve and utilizes similar techniques transferable from the use of other conventional energy devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Development of new advanced energy based surgical instruments for laparoscopic surgery have shortened the surgical procedure time and have replaced the conventional hemostasis tools such as sutures, clips and staples with fast, safe and effective hemostasis. Our study did not find significant difference between the TB and LigaSure devices, consistent with the finding of other recent publications [ 2 , 12 ]. A retrospective study from Italy compared outcomes and cost between TB and three other energy-based devices in patients undergoing laparoscopic colorectal resection, did not find any significant difference in the operative time and other outcomes between the groups [ 2 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Development of new advanced energy based surgical instruments for laparoscopic surgery have shortened the surgical procedure time and have replaced the conventional hemostasis tools such as sutures, clips and staples with fast, safe and effective hemostasis. Our study did not find significant difference between the TB and LigaSure devices, consistent with the finding of other recent publications [ 2 , 12 ]. A retrospective study from Italy compared outcomes and cost between TB and three other energy-based devices in patients undergoing laparoscopic colorectal resection, did not find any significant difference in the operative time and other outcomes between the groups [ 2 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study did not find significant difference between the TB and LigaSure devices, consistent with the finding of other recent publications [2,12]. A retrospective study from Italy compared outcomes and cost between TB and three other energy-based devices in patients undergoing laparoscopic colorectal resection, did not find any significant difference in the operative time and other outcomes between the groups [2].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have concluded that the TB can be as safe as other energy-based devices when used in laparoscopic surgery [ 20 22 ], thyroid surgery [ 11 ] and neck dissections [ 10 ]. This study has indicated that the TB is at least as safe as the SED during TL and ND, as the statistically insignificant difference was found in favor of the TB group.…”
Section: Discussionmentioning
confidence: 99%
“…The growing adoption of minimally invasive techniques in colorectal cancer surgery has led to an increasing need for safer, more efficient, reliable hemostasis, and tissue dissection 10 . Recent advances in technology of laparoscopic surgical instrumentation made laparoscopic colorectal surgery more feasible 3 .…”
Section: Discussionmentioning
confidence: 99%